Saxagliptin suppresses degradation of type II collagen and aggrecan in primary human chondrocytes: a therapeutic implication in osteoarthritis - Ning Hu; Xuan Gong; Shijie Yin; Qi Li; Hao Chen; Yuwan Li; Feilong Li; Leilei Qing; Jianye Yang; Sizheng Zhu; Jiawei Wang; Junchao Li (Artificial Cells, Nanomedicine, and Biotechnology)
Osteoarthritis (OA) is a major public health concern for which a reliable non-invasive treatment option has yet to be developed. In the present study, we investigated the effects of saxagliptin, a novel dipeptidyl peptidase IV (DPP-4) inhibitor, on several important aspects of the pathophysiology of OA using primary human chondrocytes. The results of real-time PCR and ELISA analyses show that saxagliptin treatment significantly decreased mRNA and protein expression of three key cartilage degrading enzymes: matrix metalloproteinase (MMP)-1, MMP-3, and MMP-13. The results of western blot confirmed that this decrease in MMP-1, -3, and -13 expression prevented degradation of type II collagen. We also found that saxagliptin significantly inhibited expression of a disintegrin and metalloproteinase with thrombospondin motif (ADAMTS)-4 and ADAMTS-5, which was reflected by markedly decreased degradation of aggrecan. Inhibition of DPP-4 by saxagliptin also reduced oxidative stress in human primary chondrocytes as evidenced by decreased production of reactive oxygen species (ROS) and increased glutathione (GSH) levels. Additionally, the results of western blot analysis show that the effects of saxagliptin are mediated through the p38/IκBα/NF-κB pathway, which is considered an important treatment target for OA. These findings suggest a potential role for saxagliptin as a novel treatment against OA.